2018
DOI: 10.1177/1354068818794216
|View full text |Cite
|
Sign up to set email alerts
|

The electoral cost of coalition participation

Abstract: It is a well-established empirical finding that governments on average lose votes during their time in office. This exploratory analysis examines whether all members of coalition governments suffer the electoral cost of governing equally. Using electoral data from 20 parliamentary systems from 1961 to 2015, I compare the electoral performance of junior coalition members, the prime minister of a coalition, and single-party governments. Furthermore, I examine the conditioning effects of economic performance, leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…In particular, these parties were in control of the ministry responsible for financial regulation of the mortgage market. Further, while some researchers have found that the prime minister’s party is primarily held accountable for economic conditions (Debus, Stegmaier, and Tosun 2014; Duch and Stevenson 2008; Fisher and Hobolt 2010; although see Hjermitslev forthcoming), recent studies of local economic voting tend to include government coalition partners (Elinder 2010; Simonovits, Kates, and Szeitl forthcoming). However, as we show below, excluding coalition partners does not substantially alter the results.…”
Section: Research Design and Datamentioning
confidence: 99%
“…In particular, these parties were in control of the ministry responsible for financial regulation of the mortgage market. Further, while some researchers have found that the prime minister’s party is primarily held accountable for economic conditions (Debus, Stegmaier, and Tosun 2014; Duch and Stevenson 2008; Fisher and Hobolt 2010; although see Hjermitslev forthcoming), recent studies of local economic voting tend to include government coalition partners (Elinder 2010; Simonovits, Kates, and Szeitl forthcoming). However, as we show below, excluding coalition partners does not substantially alter the results.…”
Section: Research Design and Datamentioning
confidence: 99%
“…Even within a multiparty context, different practices of executive power-sharing matter. For instance, Hjermitslev (2018) recently showed that junior partners in coalition governments are particularly hit by the cost of ruling. This raises important questions about how voters attribute negative news to different coalition partners.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on the electoral price that incumbent parties pay at the polls has demonstrated a clear link between governing and a diminished vote share in subsequent parliamentary elections (Rose and Mackie 1983;Paldam 1986;Narud and Valen 2008;Bergman and Strom 2011). On the other hand, economic voting literature has shown how economic determinants such as GDP, inflation, and unemployment rates can affect governing parties in either a positive or negative fashion (Lewis-Beck 1986;Nannestad and Paldam 1994;Lewis-Beck and Stegmaier 2000;2013;Hjermitslev 2018).…”
Section: Holding Governing Parties Accountablementioning
confidence: 99%
“…Previous research on the electoral price that incumbent parties pay at the polls has demonstrated a clear link between governing and a diminished vote share in subsequent parliamentary elections (Bergman and Strøm, 2011; Paldam, 1986; Rose and Mackie, 1983). On the other hand, economic voting literature has shown how economic determinants such as gross domestic product (GDP), inflation, and unemployment rates can affect governing parties in either a positive or negative fashion (Hjermitslev, 2020; Lewis-Beck, 1986; Lewis-Beck and Stegmaier, 2000, 2013; Nannestad and Paldam, 1994). Additionally, recent research on the electoral effect of holding a ministerial office in Ireland found that individual politicians who held a portfolio received an electoral boost over co-partisans who did not hold a ministerial office (Martin, 2016).…”
Section: Holding Governing Parties Accountablementioning
confidence: 99%